THE USE OF DIFFERENT PERCENTAGES OF WILD THYME THYMUS SERPYLLUM IN THE DIETS OF AWASSI LAMBS AND ITS EFFECT ON GROWTH AND CARCASS CHARACTERISTICS - Rashid, Abdul Majeed Khaled; Mohamed, Muthanna Ahmed (Journal of agricultural, environmental and veterinary sciences, 2021)
This study was conducted to find out the effect of using different percentages of wild thyme, Thymus serpyllum in the diets of Awassi lambs, and its effect on growth, carcass characteristics, blood traits and some properties of rumen fluid. This experiment was conducted in field of the Department of Animal Production of College of Agriculture and Forestry at University of Mosul. In this experiment, 24 twenty four male Awassi lambs were used, their ages ranged between 5-6 months, lambs were randomly distributed to 4 four treatments and each treatment included 6 six replicates of lambs. The lambs were raised and fed for a period of 90 days From date of (11/11/2020) the beginning of the experiment to date of slaughtering animals for sampling for research purposes on (9/2/2021). And lambs of first treatment (control) were fed on a standard diet only. Free from any additives consisting of barley, wheat bran, wheat straw, soybean meal, limestone and salt, a second treatment was added wild thyme 10 gm/kg feed/head daily, third treatment was 20 gm/kg feed/head daily and fourth treatment was 30 g/kg of feed/head per day. The results of experiment did not show significant differences in daily and total weight gain and carcass characteristics. The results of pH of rumen fluid before feeding or after feeding two hours, nor concentration of rumen liquid ammonia two hours after feeding did not show significant differences between the four treatments. As for the ammonia concentration of the rumen fluid before feeding, it indicated a significant superiority (P≤ 0.05) in treatment. Fourth compared to other transactions. Also, no significant differences were observed in blood characteristics.